Traces of knowledge and use of cues of sensory processing in ancient Greek art - Duarte, Antonio M.; Constantinidi, Niki P. (Arte, Individuo y Sociedad, 2022)
This study aimed to find evidence of the presence, in ancient Greek art, of cues (triggers) for sensory processes involved in the appreciation of visual arts, within the framework of the psychology of art. The presence of such cues in ancient Greek art can suggest the existence of knowledge about them, together with their use, already by ancient Greek artists. For the study, a sample of image reproductions of ancient Greek art (from the archaic to the Hellenistic period - ca. 7th - 1st century BC) was submitted to a thematic-content analysis. This analysis revealed the presence of all most relevant known cues that trigger specific sensory processes involved in visual arts appreciation. Results suggest an intuitive knowledge of these processes by ancient Greek artists (probably based both on personal experience and social sharing), which aligns with the seminal role of ancient Greek art both in the extended use of those cues in western art and in the modulation of a “western way” of appreciating art.